Implementasi Cybergogy untuk Pembelajaran PAI yang Bermakna - Umar; Jamaluddin (Prosiding Seminar Nasional Fakultas Tarbiyah dan Ilmu Keguruan IAIM Sinjai, 2023)
This paper aims to review the literature to propose a meaningful PAI learning paradigm in the context of cybergogy learning interaction. The demands of ICT needs and the meaningfulness of learning increasingly urge innovation and futuristic learning reconstruction. Empirically, since the Covid-19 pandemic passed, the challenges of PAI learning do not only include the planning, implementation and evaluation of blended learning but also the meaningfulness of learning interactions to achieve the expected goals. The cybergogy model carries aspects of knowledge (cognitive), social and emotional interestingly tracing its conceptual relevance, adaptation and implementation in learning PAI meaningfully. In addition to achieve the goal of meaningfulness of PAI learning, it is also expected to create a comfortable online learning (good online learner) in the integration of digital technology. This paper is developed through the method of reviewing relevant literature from various scientific sources with a literature approach, the data is collected and analyzed descriptively and then a paradigm is proposed that is worthy of being informed and proposed as a finding. Concept of cybergogy is actually relevant to be implemented in PAI learning, having a connection of concepts and principles to create meaningful learning, emphasizing cognitive engagement, strengthening social and emotional values of students. The meaningful PAI learning and the context of cybergogy emphasize careful interaction, namely the identification of various relevant contexts, the learning objectives are achieved comprehensively, namely the development of knowledge and continuous emotional and social growth in line with Islamic teachings. In addition, it is necessary to pay attention to pedagogical and technical principles, holistic and integrative approaches, so that they can be widely considered for learning.